2021
DOI: 10.1128/aac.01495-21
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility of 182 Fusarium Species Isolates from 20 European Centers: Comparison between EUCAST and Gradient Concentration Strip Methods

Abstract: We determined the susceptibility of 182 Fusarium spp. isolates to 5 antifungal drugs (amphotericin B, voriconazole, posaconazole, isavuconazole, terbinafine) by EUCAST method. Based on the latest taxonomic insights, isolates collected from 20 European centers were distributed into 7 complexes and 27 species. The susceptibility was variable depending on the species. Comparison with gradient concentration strips method performed for 77 isolates showed essential agreement for voriconazole, posaconazole, isavucona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…This is consistent with the findings of most studies in which amphotericin B was found to have lower MICs in vitro compared to other antifungals [4,13,[35][36][37]. As previously reported [10,31,38], the susceptibility of Fusarium to amphotericin B varied, depending on the species. Surprisingly, we observed miltefosine was found to be the most active agent against resistant and susceptible Fusarium isolates after amphotericin B. Miltefosine was initially developed as an anticancer agent, but it is now a clinically approved anti-parasitic drug against Leishmania species.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings of most studies in which amphotericin B was found to have lower MICs in vitro compared to other antifungals [4,13,[35][36][37]. As previously reported [10,31,38], the susceptibility of Fusarium to amphotericin B varied, depending on the species. Surprisingly, we observed miltefosine was found to be the most active agent against resistant and susceptible Fusarium isolates after amphotericin B. Miltefosine was initially developed as an anticancer agent, but it is now a clinically approved anti-parasitic drug against Leishmania species.…”
Section: Discussionsupporting
confidence: 92%
“…When evaluating potential cut-off values for the definition of reduced susceptibility, significant variation is noted across three primary species complexes based around Fusarium solani, Fusarium oxysporum, and Fusarium verticillioides , although this does not encompass all pathogenic species. 102 , 103 In spite of this variability and high rates of resistance to the most commonly used agents (amphotericin B, mould-active triazoles), cure is feasible and in vitro resistance is not consistently predictive of clinical outcomes; resolution of neutropenia was associated with a greater likelihood of clinical success. 104 , 105 This discrepancy emphasizes the need to devise a means for prospective trials aimed at these rare moulds to achieve better data-driven treatment approaches.…”
Section: Methods Of Antifungal Resistance Testingmentioning
confidence: 99%
“…Infections by species of the FSSC are problematic because most are innately resistant to mainstream azole antifungals, including voriconazole [ 29 , 30 ], which is the recommended treatment option for invasive fusariosis (IF) [ 31 , 32 ]. Amphotericin B seems to be the only antifungal to which most FSSC species are susceptible [ 29 , 30 ]. This hinders the efficacy of treating immunocompromised patients with IF [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%